2007
DOI: 10.1111/j.1365-2559.2007.02665.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of TWIST and E‐cadherin expression in the metastatic progression of prostatic cancer

Abstract: These results suggest that TWIST may serve as a prognostic marker for high-grade prostatic cancer. In addition, up-regulation of TWIST in combination with aberrant E-cadherin expression in primary prostatic cancer specimens may predict development of distal metastatic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
98
1
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 33 publications
(73 reference statements)
4
98
1
10
Order By: Relevance
“…another study also showed nuclear immunoreaction with Twist in high-grade squamous cell carcinoma (12). according to invasive behavior of adCC, our results support previous studies that have shown a relationship between nuclear Twist expression and increasing tumor invasiveness (10,19).…”
supporting
confidence: 81%
See 2 more Smart Citations
“…another study also showed nuclear immunoreaction with Twist in high-grade squamous cell carcinoma (12). according to invasive behavior of adCC, our results support previous studies that have shown a relationship between nuclear Twist expression and increasing tumor invasiveness (10,19).…”
supporting
confidence: 81%
“…Twist includes two proteins: Twist1 and Twist2, which have shown similar expression in tumors (8). Twist expression was previously shown in some normal tissues such as prostate and breast (11,19). it was also demonstrated that this protein showed higher expression in malignant tumors compared to benign tumors such as prostate, parathyroid and lung (19)(20)(21).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…TWIST also enhances AKT2 expression, inhib-its p53 function and cell apoptosis, mediates HIF-1α-enhanced cancer progression, promotes cell survival, and contributes to oncogenesis, angiogenesis and acquired Taxol resistance [7,[10][11][12][13][14]. In agreement with these critical roles in cancer cells, TWIST is overexpressed in breast, gastric, hepatocellular, prostate and bladder cancers, and its upregulation correlates with low E-cadherin expression, high cancer aggressiveness and poor survival rate [3,8,[15][16][17][18][19]. These studies clearly demonstrate that TWIST is a master transcription factor that controls EMT, cancer progression and metastasis and a useful molecular target for treatment of cancer metastasis.…”
Section: Introductionmentioning
confidence: 65%
“…TWIST1, a helix-loop-helix transcription factor, is highly expressed in many types of human cancers (44). Recently, TWIST1 was suggested to be an oncogene (23,45,46) and confers prostate cancer cells with an enhanced metastatic potential through promoting EMT, and a high TWIST1 expression in human prostate cancer is associated with an increased metastatic potential (47). However, we did not find dihydrotestosterone to effect the TWIST1-regulated and/or EMT-related genes such as CDH1, SNAIL, and vimentin expression in LNCaP cells ( Fig.…”
Section: Discussionmentioning
confidence: 99%